"Hold them or fold them:" evidence-based decisions to discontinue investigations of non-domestic minor violence. Issue 4 (2nd August 2021) - McFadzien, Kent; Sherman, Lawrence W.
Abstract : Purpose: The purpose of this paper is to demonstrate a "maintenance pathway" for ensuring a low false negative rate in closing investigations unlikely to lead to a clearance (detection). Design/methodology/approach: A randomised controlled experiment testing solvability factors for non-domestic cases of minor violence. Findings: A random selection of 788 cases, of which 428 would have been screened out, were sent forward for full investigation. The number of cases actually detected was 22. A total of 19 of these were from the 360 recommended for allocation. This represents an improvement of accuracy over the original tests of the model three years earlier. Research limitations/implications: This study shows how the safety of an investigative triage tool can be checked on a continuous basis for accuracy in predicting the cases unlikely to be solved if referred for full investigations. Practical implications: This safety check pathway means that many more cases can be closed after preliminary investigations, thus saving substantial time for working on cases more likely to yield a detection if sufficient time is put into the cases. Social implications: More offenders may be caught and brought to justice by using triage with a safety backstop for accurate forecasting. Originality/value: This is the first published study of a maintenance pathway based on a random selection of cases that would otherwise not have been investigated. If widely applied, it could yield far greater time for police to pursue high-harm, serious violence.